Accounting for the SES-Math Achievement Gap at School Entry: Unique Mediation Paths via Executive Functioning and Behavioral Self-Regulation - Ng, Ee Lynn; Bull, Rebecca; Khng, Kiat Hui (Frontiers in Education, 2021)
Childhood socioeconomic status (SES) is strongly predictive of math achievement in early childhood and beyond. In this study, we aimed to further our understanding of the mechanisms underpinning the SES-achievement gap by examining whether two aspects of self-regulation—executive functions (EF) and behavioral self-regulation (BSR)—mediate between SES and math achievement. Using data from a longitudinal study in Singapore (N=1257, 49% males), we examined the predictive link from SES to math achievement at entry to formal education (age 7), and the role of EF (child-assessed) and BSR (child-assessed and teacher-rated) as mediators of the SES-math achievement relationship. After accounting for children’s non-verbal reasoning and prior math achievement, EF and BSR (both child-assessed) emerged as significant partial mediators between SES and math. A key contribution of our study is in demonstrating that both components of self-regulation play a small role in explaining SES disparities in math achievement. Our findings further suggest that a balanced focus on enhancing EF and BSR skills of children from low-SES families may help to attenuate the SES-math achievement gap. More generally, our research contributes new insights to the ongoing debate about the theoretical distinctions between EF and BSR.